1982
DOI: 10.3758/bf03209220
|View full text |Cite
|
Sign up to set email alerts
|

The mental representation of spatial descriptions

Abstract: Two experiments investigated the mental representation of spatial descriptions. In Experi· ment 1, the subjects classified a series of diagrams, each presented after a spatial description, as either consistent or inconsistent with the description. They were then given an unexpected recognition test of their memory for the descriptions. The subjects remembered the meanings of determinate descriptions very much better than those of grossly indeterminate descriptions; their memory for a description was not reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
3
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(185 citation statements)
references
References 13 publications
6
175
3
1
Order By: Relevance
“…One explanation of these results lies in the neural basis of mental images of geometric figures. Previous studies have shown that words referring to spatial representations can elicit the processing of spatial figures (e.g., Hayward and Tarr, 1995;Mani and Johnson-Laird, 1982) and that spatial processing is subserved by the parietal cortex (e.g., Hilgetag et al, 2001), especially the inferior parietal lobule (e.g., Alivisatos and Petrides, 1997;Carpenter et al, 1999). Geometric terms as well as numbers also had greater activation than algebraic terms and tool words at the posterior superior parietal lobe as shown in the ROI analysis based on Dehaene et al's three parietal circuit model.…”
Section: The Intraparietal Sulcus and The Processing Of Mathematical mentioning
confidence: 99%
“…One explanation of these results lies in the neural basis of mental images of geometric figures. Previous studies have shown that words referring to spatial representations can elicit the processing of spatial figures (e.g., Hayward and Tarr, 1995;Mani and Johnson-Laird, 1982) and that spatial processing is subserved by the parietal cortex (e.g., Hilgetag et al, 2001), especially the inferior parietal lobule (e.g., Alivisatos and Petrides, 1997;Carpenter et al, 1999). Geometric terms as well as numbers also had greater activation than algebraic terms and tool words at the posterior superior parietal lobe as shown in the ROI analysis based on Dehaene et al's three parietal circuit model.…”
Section: The Intraparietal Sulcus and The Processing Of Mathematical mentioning
confidence: 99%
“…Furthermore, the structure of spatial descriptions affects the construction. In studies of spatial mental models, descriptions were easier to transform into mental models when they were determinate (Baguley & Payne, 2000;Mani & Johnson-Laird, 1982), continuous (Denis & Cocude, 1992;Ehrlich & Johnson-Laird, 1982;Oakhill & Johnson-Laird, 1984), and condensed (Zwaan & van Oostendorp, 1994).…”
Section: Preconditions Of Spontaneous Spatial Situation Model Construmentioning
confidence: 99%
“…If subjects read a text accompanied by a map, they can inspect the map to encode the spatial relations between objects directly, eliminating the need to make spatial inferences. Second, a text does not usually give exact metric information about the location of landmarks and is thus indeterminate, although, interestingly, readers seem to use default values to infer locations of objects when exact distance information is not given (Mani & Johnson-Laird, 1982). A map is determinate in that each landmark is depicted in a specific location.…”
Section: Factors Influencing Cognitive Map Constructionmentioning
confidence: 99%
“…Cognitive psychologists and human geographers have been interested in studying the nature of the representations that people construct from these different experiences. One line of research has shown that people construct "mental models" from text, which are representations of the objects or situations described in a text (Byrne & Johnson-Laird, 1989;Johnson-Laird, 1983;Mani & Johnson-Laird, 1982) and not just "text-based" representations of the propositional content of the text (van Dijk & Kintsch, 1983). In addition to representing the relations between landmarks that were explicitly described in the text, mental models of spatial environments allow inferences about all possible relations between landmarks (Kulhavy, Schwartz, & Shaha, 1983;Perrig & Kintsch, 1985;Taylor & Tversky, 1992a, 1992b.…”
mentioning
confidence: 99%